Exercise dependence and overtraining: The physiological and psychological consequences of excessive exercise - Adams, J.; Kirkby, R. J. (Sports Medicine, Training and Rehabilitation, 2001)
Overtraining is a condition in which the physiological demand of an exercise regime outweighs the ability of the body to adjust to the demand. The consequences of overtraining are widespread, negatively affecting several physiological systems, including the neuroendocrine, immunological, cardiovascular, and musculoskeletal systems, respectively. Overtraining could also result in several negative psychological disturbances. Exercise dependence a pathology in which a person becomes addicted to exercise, often exercising twice or more daily, while experiencing physical and psychological withdrawal symptoms is also a probable cause of overtraining. Because of his or her excessive exercising, a person diagnosed with exercise dependence is equally as vulnerable to overtraining as the committed athlete.